Brain atrophy and cholinergic denervation in progressive supranuclear palsy: an MRI and [18F]-FEOBV PET study - Kanel, Prabesh; Roytman, Stiven; Carli, Giulia; Vangel, Robert; Barr, Jaimie; Michalakis, Fotini; Spears, Christopher Chauncey; Scott, Peter J. H.; Albin, Roger L.; Bohnen, Nicolaas I. (Frontiers in Neuroscience, 2025)
IntroductionProgressive supranuclear palsy (PSP) is a neurodegenerative disorder characterized by a wide spectrum of motor and cognitive impairments. Structural brain imaging biomarkers, such as the Magnetic Resonance Parkinsonism Index 2.0 (MRPI 2.0), are increasingly recognized as means of supporting a PSP diagnosis. These anatomic measures lack neurobiological correlates. In the present work, we investigated whether structural brain changes captured by MRPI 2.0 associate with whole-brain and regional cholinergic nerve terminal deficits in PSP.MethodsStructural magnetic resonance (MR) and vesicular acetylcholine transporter (VAChT) [18F]-fluoroethoxybenzovesamicol ([18F]-FEOBV) PET imaging was obtained in a sample of 16 PSP subjects. MRPI 2.0 index was quantified and correlated with whole brain VAChT binding using statistical parametric mapping (SPM), after adjustment for sex, dopaminergic medication dose and disease duration. Post hoc multiple regression analyses were performed to correlate regional mean VAChT binding with MRPI 2.0 (after adjusting for the same covariates), characterizing the proportion of variance in cholinergic terminal deficits explained by this structural index.ResultsVoxel-wise SPM analyses revealed that MRPI 2.0 is significantly associated with cholinergic nerve terminal loss in brainstem, especially pontomesencephalic, limbic structures, insula, basal ganglia, thalamus, and cerebellar regions. Post hoc multiple regression analysis demonstrated that MRPI 2.0 accounts for about half of the variance in cholinergic nerve terminal integrity within relevant brain structures in PSP, showing the most robust association in the thalamus.DiscussionStructural brain changes associated with higher MRPI 2.0 index scores may be a reliable proxy measure of cholinergic terminal deficits in PSP, predominantly those in subcortical regions. Differential association of subcortical brain region cholinergic deficits with PSP-specific structural brain changes may reflect the characteristic pattern of 4R-tau pathology observed in PSP.